MELIHAT SIKAP HOSPITALITAS KRISTEN BERDASARKAN ANALISIS TEOLOGIS LUKAS 10:25-37 DAN IMPLIKASINYA TERHADAP UPAYA PENCEGAHAN KONFLIK AGAMA DI INDONESIA - Taruk La'bi, Delchy; Parura, Mila; Mari'pi, Yanti (Sekolah Tinggi Teologi Hagiasmos Mission, 2023)
As social beings, humans are never free from conflict. As social beings too, humans need other people while still being hospitable/hospitality to stay harmonius in living together. But the fact is that the attitude of hospitality is an attitude that is stilldifficult to do. It is proven there are still many conflicts going on, especially religious conflicts in Indonesia, which are motivated by various differences. The purpose of this research is to see Christian hospitality based on Lukw 10:25-37 as a solution to prevent religious conflicts from occurring. Through descriptive qualitative methods, it was concluded that the hospitality attitude shown by the Samaritans, who are open and tolerant of differences can be applied as an effort to prevent religious conflicts in Indonesia. Keywords: Hospitality; Samaritans; Religoious Conflict.